Performance measurement for pension fund trustees - Brown, Gavin; Chartered Institute of Management Accountants (London : Chartered Institute of Management Accountants, 1994)
This research study examines the practice of fund managers who strive for short-term gains for their trustees, which in turn has a negative effect on the long-term needs of the industry.
Includes bibliographical references.
oif 31/03/2015
Loans
Keywords: Pension trusts--Evaluation; Pension trusts--Management; Great Britain